STUDI LITERATURE: EFEKTIVITAS PEMBERIAN MINUMAN KUNYIT ASAM TERHADAP PENURUNAN DISMENOREA PADA REMAJA PUTRI - Marwasariaty; Hasna; Ulul Asmy (Institut Kesehatan Hermina, 2024)
Menstruation can be defined as periodic bleeding from the uterus that occurs monthly and throughout a woman's active reproduction (Michael et al., 2020). The menstrual cycle occurs periodically every month with a normal range of 28 days, while the menstrual cycle itself is 3 to 7 days (Rahayu et al., 2017). Dsimenorrhea is pain felt in the lower abdomen or cramps before menstruation which lasts 2-3 days, starting the day before menstruation begins (Andriana, 2018). Dysmenorrhea is divided into two, namely primary and secondary dysmenorrhea. Primary dysmenorrhea is dysmenorrhea that occurs without any abnormalities in the reproductive organs. Meanwhile, secondary dysmenorrhea is dysmenorrhea associated with abnormalities in the reproductive organs, such as endometriosis, adenoma, and uterine myoma (Osuga et al., 2020). One of the interventions to treat dysmenorrhea is Turmeric Acid Drink. Purpose: the writing of this Literature Review is to analyze the effectiveness of giving sour turmeric drink on reducing dysmenorrhea pain. Design: what was used was Literature Review using articles published in the period 2018-2023, out of 247 found on Google Scholar that met the inclusion and exclusion criteria, 3 articles were obtained. Method: PICO framework format with keywords tailored to topics related to the effectiveness of giving sour turmeric drink on reducing dysmenorrhea pain. Results: from the review of the four journals concluded that there was a significant effect of giving sour turmeric drink on reducing dysmenorrhea. Conclusion: There is an effect of the effectiveness of sour turmeric drink on reducing dysmenorrhea.